Profile of Students' Creative Thinking Skills on Newton's Laws - Amelia Dafera; Yudi Kurniawan; Riski Muliyani; Sharon Sharon (STKIP Singkawang, 2025)
This study aims to provide a profile overview of the students' creative thinking skills on Newton's Laws. The research used was a descriptive quantitative method. The research was conducted on grade VIII students at one of the State Junior High Schools in Singkawang City. The subjects in this study were selected by purposive sampling totaling 36 students. The research data was collected using a creative thinking skills test totaling 8 essay questions. Data were analysed using descriptive percentages. The results of the study showed that (1) students who were at a medium level of creative thinking were 81%, students who were at a low level of creative thinking skills were 19%; (2) the percentage results of creative thinking skills per indicator, namely fluency 69.17%, flexibility 57.92%, originality 37.50%, and elaboration 50.83%. Thus, it can be concluded that students' creative thinking skills were still low.